Flexible negative electrode paper for solid-state battery as well as preparation method and application of flexible negative electrode paper

Porous carbon nanotubes were prepared by catalytic pyrolysis and combined with silicon deposition and carbon coating to build a conductive network to prepare flexible silicon carbon negative electrode paper, which solved the shortcomings of solid-state battery negative electrode materials in terms of energy density and cycle life, and achieved efficient and stable battery performance.

CN119786543AActive Publication Date: 2025-04-08HUBEI JIANGXIN NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411976414.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing solid-state battery anode materials have shortcomings in terms of high energy density and long cycle life, especially the lithium metal anode is hindered by the formation of lithium dendrites and unstable interface contact, and traditional graphite anodes are also difficult to meet the needs of high energy density.

Method used

A catalytic pyrolysis reaction after mixing nitrogen-containing molecules with transition metal salts was used to prepare porous carbon nanotubes with wide diameters, and silicon carbon negative electrodes were obtained through silicon deposition and carbon coating. Then, an electronic/ion conductive network is constructed using conductive carbon materials and solid electrolytes, and a flexible negative electrode paper is prepared in combination with nanocellulose.

Benefits of technology

The prepared flexible negative electrode paper exhibits excellent cycle stability, rate performance and low expansion rate in solid-state batteries, while having high first-term efficiency and high capacity, solving the problems of lithium dendrites and low conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786543A_ABST
    Figure CN119786543A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of flexible negative electrode paper for a solid-state battery, which comprises the following steps: (S1) uniformly mixing nitrogen-containing molecules and transition metal salt, performing catalytic pyrolysis to obtain carbon nanotubes, and performing physical activation pore-forming, silicon deposition and carbon coating to obtain a silicon-carbon negative electrode; (S2) mixing a silicon-carbon negative electrode, a dispersing agent and a solvent I to obtain a silicon-carbon dispersion liquid A; mixing a conductive carbon material, a solid electrolyte, a polymer and a solvent II to obtain electron / ion conductive slurry B; mixing nano cellulose with a solvent III to obtain a fiber dispersion emulsion C; mixing and dispersing the three components to obtain papermaking pulp; and (S3) coating a substrate with the papermaking slurry, and carrying out reduction treatment with an amino-containing micromolecular reducing agent to obtain the flexible negative paper for the solid-state battery. A solid-state battery assembled by taking the flexible negative electrode paper prepared by the invention as a negative electrode has excellent cycling stability, rate capability and low expansion rate, and has high first efficiency and high capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and specifically relates to a flexible negative electrode paper for solid-state batteries and a preparation method and application thereof. Background Art

[0002] Solid-state battery anode materials are currently in a rapid development stage. Lithium metal, with its high theoretical capacity and low potential advantages, is considered to be the final form of battery anode, especially solid-state battery anode materials. However, the formation of lithium dendrites and unstable interface contact have hindered the extensive application of lithium metal anodes. Traditional anode materials such as graphite are difficult to meet the requirements of solid-state batteries for high energy density and long cycle life. Therefore, researchers are actively developing new anode materials, among which silicon-carbon anode materials have attracted much attention.

[0003] Silicon-carbon anode materials have the advantage of high energy density, and their theoretical specific capacity is much higher than that of graphite anode. However, due to the large volume expansion of nano-silicon particles and relatively low conductivity, research on silicon-carbon materials in solid-state batteries is still ongoing. Summary of the invention

[0004] In response to the above problems, the present invention discloses a method for preparing flexible negative electrode paper for solid-state batteries. The solid-state battery assembled using the prepared flexible negative electrode paper as the negative electrode has excellent cycle stability, rate performance and low expansion rate, and has both high initial efficiency and high capacity.

[0005] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0006] In a first aspect, the present invention provides a method for preparing a flexible negative electrode paper for a solid-state battery, comprising:

[0007] (S1) uniformly mixing nitrogen-containing molecules and transition metal salts, obtaining carbon nanotubes through catalytic pyrolysis reaction, and then obtaining porous carbon nanotubes through physical activation and pore formation; using the porous carbon nanotubes as a substrate, sequentially performing silicon deposition and carbon coating to obtain a silicon-carbon negative electrode;

[0008] (S2) mixing a silicon-carbon negative electrode, a dispersant and a solvent I to obtain a silicon-carbon dispersion A; mixing a conductive carbon material, a solid electrolyte, a polymer and a solvent II to obtain an electronic / ion conductive slurry B; mixing nanocellulose with a solvent III to obtain a fiber dispersion emulsion C; mixing and dispersing the silicon-carbon dispersion A, the electronic / ion conductive slurry B and the fiber dispersion emulsion C to obtain a papermaking pulp;

[0009] The conductive carbon material includes a one-dimensional carbon material and an optionally added two-dimensional carbon material;

[0010] (S3) The papermaking slurry is coated on a substrate, and is reduced with an amine-containing small molecule reducing agent to obtain the flexible negative electrode paper for solid-state batteries.

[0011] The preparation method disclosed in the present invention first uses nitrogen-containing molecules as raw materials to prepare wide-diameter carbon nanotubes (average diameter of 100-800nm) through catalytic pyrolysis. The diameter is much larger than that of carbon nanotubes prepared by conventional methods (average diameter is mostly below 50nm). Then, the porous carbon nanotubes obtained after activation are used as a substrate for silicon and carbon deposition to prepare a flexible silicon-carbon negative electrode with low expansion rate. Furthermore, a complete electronic / ion conductive network is constructed with conductive carbon materials and solid electrolytes, so that lithium ions and electrons can fully interact with the silicon-carbon negative electrode for electrical contact, solve the problem of uneven deposition of lithium ions, reduce the generation of lithium dendrites, significantly improve the overall rate performance of the negative electrode, and do not need to use copper foil current collectors, reduce the total mass of the battery, and improve the energy density. At the same time, the flexible conductive carbon material and the rigid solid electrolyte jointly form a "soft-hard" skeleton, which ensures the flexibility of the negative electrode sheet while further reducing the volume expansion of the silicon-carbon negative electrode. In addition, the prepared paper is a flexible paper that can be quickly cut into any shape and has no obvious expansion during the battery cycle.

[0012] In step (S1):

[0013] In an optional embodiment, the nitrogen-containing molecule is selected from one or more of urea, dicyandiamide, molecules having a triazine structure and hybrid derivatives thereof, amino acids and derived polypeptides thereof;

[0014] Optionally, the molecule having a triazine structure and its hybrid derivatives are selected from 1,2,3-triazine, 1,2,4-triazine, 1,3,5-s-triazine, 1-hydrogen-1,2,4-triazole, 4-hydrogen-1,2,3-triazole, and 4-hydrogen-1,2,4-triazole.

[0015] Optionally, the amino acid and its derivative polypeptide are selected from guanine, leucine, etc., and small molecule peptide chains formed therefrom.

[0016] Optionally, the molar mass of the nitrogen-containing molecule is 10 to 1500 g / mol;

[0017] Further optionally, the molar mass of the nitrogen-containing molecule is 10 to 500 g / mol.

[0018] In an optional embodiment, the transition metal salt, the cation includes but is not limited to one or more of Fe(III / II), Co(II), Ni(II), Cu(II), Zn(II), Mn(II), and the anion includes but is not limited to one or more of nitrate ion, chloride ion, and sulfate ion;

[0019] Optionally, the cation is selected from Fe(III) and / or Co(II);

[0020] Optionally, the anion is selected from nitrate ions.

[0021] In an alternative embodiment:

[0022] The mass ratio of nitrogen-containing molecules to transition metal salts is 10:(0.1-1.5);

[0023] The catalytic pyrolysis temperature is 600-1000°C;

[0024] The carbon nanotubes prepared by the catalytic pyrolysis have an average tube diameter of 100 to 800 nm.

[0025] Experiments have found that by adjusting the mass ratio of nitrogen-containing molecules to transition metal salts, the average diameter of the prepared carbon nanotubes can be controlled, and then the electrochemical properties of the final negative electrode paper and the solid-state battery assembled therein can be regulated.

[0026] Optionally, the mass ratio of nitrogen-containing molecules to transition metal salt is 10:(0.25-0.75);

[0027] Further optionally, the mass ratio of the nitrogen-containing molecules to the transition metal salt is 10:(0.25-0.5).

[0028] Optionally, the heating rate of the catalytic pyrolysis is 2 to 20° C. / min, and the insulation time is 1 to 6 hours.

[0029] Optionally, the crude product obtained after the catalytic pyrolysis reaction is further subjected to acid washing and drying steps;

[0030] Optionally, the acid concentration in the pickling step is 0.1 to 2 mol / L;

[0031] Optionally, the pickling time is 2 to 20 hours;

[0032] Optionally, the drying temperature is 50 to 80° C., and the drying time is 1 to 10 hours.

[0033] In step (S1):

[0034] In an optional embodiment, the physical activation pore formation satisfies at least one of the following A to D:

[0035] A. The physical activation pore forming agent is selected from CO, CO 2 , water vapor, oxygen or one or more thereof;

[0036] Optionally, the activator is selected from CO, CO 2 , water vapor;

[0037] B. The physical activation pore formation, the activator flow rate is 0.1 ~ 20L / min;

[0038] Optionally, the activator flow rate is 5 to 10 L / min;

[0039] C. The physical activation pore-forming process has a temperature of 600 to 1200°C;

[0040] Optionally, the heating rate is 0.1 to 10°C / min;

[0041] Further optionally, the heating rate is 1 to 10°C / min;

[0042] D. The physical activation pore-forming time is 1 to 15 hours;

[0043] Optionally, the physical activation pore making is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 1 to 20 rpm.

[0044] In an optional embodiment, the silicon deposition satisfies at least one of the following a to f:

[0045] a. The silicon deposition, the raw material gas used includes a silicon source gas;

[0046] Optionally, the silicon source gas includes but is not limited to common types such as monosilane, disilane, monochlorosilane, trichlorosilane, etc.;

[0047] b. The silicon deposition, the flow rate of the raw gas is 1 to 200 L / h;

[0048] Optionally, the flow rate of the raw gas is 50 to 150 L / h;

[0049] c. The silicon is deposited at a temperature of 300 to 600°C;

[0050] Optionally, the heating rate is 1 to 10°C / min;

[0051] d. The silicon deposition time is 1 to 50 hours;

[0052] e. The raw gas also includes a carrier gas;

[0053] Optionally, the carrier gas is nitrogen and / or argon;

[0054] f. Taking the total volume of the raw gas as 100%, the volume of the carrier gas accounts for 1 to 30%.

[0055] In an optional embodiment, the carbon coating satisfies at least one of the following 1) to 6):

[0056] 1) The carbon coating uses a raw material gas including a carbon-containing gas;

[0057] 2) The carbon-coated carbon-containing gas is selected from one or more of C1-C4 alkanes (methane, ethane, propane, butane), C2-C4 olefins (ethylene, propylene, butene, 1,3-butadiene), and C2-C4 alkynes (acetylene, propyne, butyne);

[0058] 3) The carbon coating has a flow rate of 1 to 100 L / h of raw gas;

[0059] 4) The carbon coating is carried out at a temperature of (400-1200)°C;

[0060] 5) The carbon coating time is 1 to 20 hours;

[0061] 6) In the carbon coating, the raw gas also includes an inert gas, and the volume proportion of the inert gas is 1 to 30% based on the total volume of the raw gas as 100%.

[0062] In step (S2):

[0063] In an optional embodiment, the dispersant is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives;

[0064] In an optional embodiment, the solvent I is selected from deionized water and / or N-methylpyrrolidone;

[0065] In an optional embodiment, in the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode, the dispersant, and the solvent I is 10:(0.01-5):(10-300);

[0066] Optionally, in the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode, the dispersant and the solvent I is 10:(0.15-0.5):(10-300);

[0067] Further optionally, in the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode, the dispersant and the solvent I is 10:(0.25-0.5):(10-300).

[0068] In an optional embodiment, the one-dimensional carbon material is selected from one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon fibers;

[0069] Optionally, when single-walled carbon nanotubes are selected, the intensity of the G band / D band in the Raman spectrum thereof is not less than 5, the average length is not less than 100 μm, and the diameter is 2 to 15 nm;

[0070] Optionally, when other one-dimensional carbon materials are selected, the G-band / D-band intensity is not less than 1, the length is not less than 5 μm, and the diameter is not higher than 50 nm.

[0071] In an optional embodiment, the two-dimensional carbon material is selected from graphene oxide;

[0072] Optionally, the two-dimensional graphene oxide is prepared by a Hammer method, and has an oxygen content of not less than 20%.

[0073] In an optional embodiment, the solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium silicon oxide, and lithium lanthanum titanium oxide;

[0074] In an optional embodiment, the polymer is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives;

[0075] In an optional embodiment, the solvent II is selected from deionized water and / or N-methylpyrrolidone;

[0076] In an optional embodiment, in the electronic / ion conductive slurry B, the mass ratio of the conductive carbon material, the solid electrolyte, the polymer and the solvent II is 1:(0.1-10):(0.1-10):(10-300);

[0077] Optionally, the mass ratio of the conductive carbon material, the solid electrolyte, the polymer and the solvent II is 1:(0.5-5):(0.5-5):(10-100);

[0078] In an optional embodiment, the mass ratio of the one-dimensional carbon material to the two-dimensional carbon material is 1:(0-1);

[0079] Optionally, the mass ratio of the one-dimensional carbon material to the two-dimensional carbon material is 1:(0.01-0.5).

[0080] Experiments have shown that the additional introduction of two-dimensional carbon materials can further improve the conductivity of the system, and the first coulombic efficiency, cycle retention rate and rate performance of the finally assembled solid-state battery are all improved.

[0081] Comparative tests have shown that using only two-dimensional carbon materials or three-dimensional carbon materials (such as acetylene black) to replace one-dimensional carbon materials will lead to deterioration of the cycle retention rate and rate performance of the final assembled solid-state battery.

[0082] In an optional embodiment, the nanocellulose has a diameter of 1 to 50 nm and a length of 30 to 100 μm;

[0083] In an optional embodiment, the solvent III is selected from deionized water and / or N-methylpyrrolidone;

[0084] In an optional embodiment, the solid content of the fiber dispersion emulsion C is 1 to 50 wt %;

[0085] In an optional embodiment, the mass ratio of the silicon-carbon dispersion A, the electronic / ion conductive slurry B, and the fiber dispersion emulsion C is 10:(1-10):(1-10);

[0086] Optionally, the mass ratio of the silicon-carbon dispersion A, the electronic / ion conductive slurry B and the fiber dispersion emulsion C is 10:(2.5-5):(2.5-5);

[0087] The experiment found that by optimizing the ratio of the above raw materials in the papermaking pulp, the electrochemical performance of the final prepared negative electrode paper and the solid-state battery assembled therein can be regulated;

[0088] Further optionally, the mass ratio of the silicon-carbon dispersion A, the electron / ion conductive slurry B and the fiber dispersion emulsion C is 10:5:5.

[0089] Optionally, the mixing and dispersing has a dispersing rate of 500 to 3000 rpm and a dispersing time of 0.5 to 10 h.

[0090] In step (S2):

[0091] In an optional embodiment, the fiber dispersion emulsion C satisfies at least one of the following (1) to (2):

[0092] (1) The fiber dispersion emulsion C also includes elastic fibers;

[0093] Optionally, the elastic fiber is selected from one or more of polytetrafluoroethylene fiber, polyvinylidene fluoride fiber, and polysiloxane fiber;

[0094] Optionally, the mass ratio of nanocellulose to elastic fiber is (0.2-5):1;

[0095] Optionally, firstly, nanocellulose is dispersed in solvent III to obtain nanocellulose dispersion, then elastic fibers are dispersed in solvent III to obtain elastic fiber dispersion, and finally the two are evenly mixed to obtain fiber dispersion emulsion C;

[0096] Optionally, the concentration of the nanocellulose dispersion is 0.1 to 10 wt %;

[0097] Optionally, the concentration of the elastic fiber dispersion is 0.1 to 10 wt %;

[0098] Optionally, the volume ratio of the nanocellulose dispersion to the elastic fiber dispersion is (0.2-5):1.

[0099] Experiments have found that the introduction of elastic fibers further improves the stability of the negative electrode sheet, giving it certain mechanical properties while also making it flexible, so that the negative electrode sheet can be cut arbitrarily without causing structural defects, and the elastic fibers can further overcome the volume expansion of silicon-carbon.

[0100] (2) The nanocellulose is subjected to copper modification treatment, specifically comprising:

[0101] The nanocellulose is immersed in a copper salt aqueous solution, and after washing, the copper-modified nanocellulose is obtained;

[0102] Optionally, the concentration of the copper salt aqueous solution is 1 to 20 wt %.

[0103] Optionally, the anion of the selected copper salt includes, but is not limited to, one or more of nitrate, chloride, and sulfate.

[0104] In step (S3):

[0105] In an optional embodiment, the amine-based small molecule reducing agent is selected from hydrazine hydrate and / or ethylenediamine;

[0106] Optionally, the amino-based small molecule reducing agent is selected from hydrazine hydrate with stronger reducing properties.

[0107] In an optional embodiment, the amine-based small molecule reducing agent is subjected to reduction treatment in a vapor state;

[0108] In an optional embodiment, the steam containing the amine-based small molecule reducing agent also includes water vapor;

[0109] In an optional embodiment, the mass fraction of the amine-based small molecule reducing agent is 0.1 to 3% based on the total mass of the steam as 100%;

[0110] Optionally, the mass fraction of the amine-based small molecule reducing agent is 1-2%.

[0111] In an optional embodiment, the temperature of the reduction treatment is 80 to 120°C;

[0112] Optionally, the reduction treatment time is 5 to 12 hours.

[0113] In a second aspect, the present invention also provides a flexible negative electrode paper for solid-state batteries prepared according to the method.

[0114] In a third aspect, the present invention further provides a negative electrode plate, which is prepared by impregnating the flexible negative electrode paper for solid-state batteries with an electrolyte.

[0115] In a fourth aspect, the present invention further provides a solid-state battery, comprising the negative electrode plate described above.

[0116] Compared with the prior art, the present invention has the following beneficial results:

[0117] The present invention discloses a method for preparing flexible negative electrode paper for solid-state batteries, which takes silicon as the core active material, and uses nitrogen-containing molecules as raw materials to prepare wide-diameter porous carbon nanotubes (average diameter is 100-800nm) through catalytic pyrolysis as the substrate, and then combines them with an electronic / ion conductive network constructed with conductive carbon materials and solid electrolytes to prepare soft and elastic negative electrode sheets, thereby solving the current problem of obvious expansion and low conductivity of silicon-carbon negative electrodes.

[0118] The solid-state battery assembled with the flexible negative electrode paper prepared by the present invention as the negative electrode has excellent cycle stability, rate performance and low expansion rate, and has both high initial efficiency and high capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0119] Figure 1 This is a schematic diagram of the preparation process of a flexible negative electrode paper for solid-state batteries disclosed in the present invention. DETAILED DESCRIPTION

[0120] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0121] In the description of the present invention, it should be noted that, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances. Below, according to the overall structure of the present invention, its embodiments are described. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.

[0122] In a first aspect, the present invention provides a method for preparing a flexible negative electrode paper for a solid-state battery, comprising:

[0123] (S1) uniformly mixing nitrogen-containing molecules and transition metal salts, obtaining carbon nanotubes through catalytic pyrolysis reaction, and then obtaining porous carbon nanotubes through physical activation and pore formation; using the porous carbon nanotubes as a substrate, sequentially performing silicon deposition and carbon coating to obtain a silicon-carbon negative electrode;

[0124] (S2) mixing a silicon-carbon negative electrode, a dispersant and a solvent I to obtain a silicon-carbon dispersion A; mixing a conductive carbon material, a solid electrolyte, a polymer and a solvent II to obtain an electronic / ion conductive slurry B; mixing nanocellulose with a solvent III to obtain a fiber dispersion emulsion C; mixing and dispersing the silicon-carbon dispersion A, the electronic / ion conductive slurry B and the fiber dispersion emulsion C to obtain a papermaking pulp;

[0125] The conductive carbon material includes a one-dimensional carbon material and an optionally added two-dimensional carbon material;

[0126] (S3) The papermaking slurry is coated on a substrate, and is reduced with an amine-containing small molecule reducing agent to obtain the flexible negative electrode paper for solid-state batteries.

[0127] The preparation method disclosed in the present invention first uses nitrogen-containing molecules as raw materials to prepare wide-diameter carbon nanotubes (average diameter of 100-800nm) through catalytic pyrolysis. The diameter is much larger than that of carbon nanotubes prepared by conventional methods (average diameter is mostly below 50nm). Then, the porous carbon nanotubes obtained after activation are used as a substrate for silicon and carbon deposition to prepare a flexible silicon-carbon negative electrode with low expansion rate. Furthermore, a complete electronic / ion conductive network is constructed with conductive carbon materials and solid electrolytes, so that lithium ions and electrons can fully interact with the silicon-carbon negative electrode for electrical contact, solve the problem of uneven deposition of lithium ions, reduce the generation of lithium dendrites, significantly improve the overall rate performance of the negative electrode, and do not need to use copper foil current collectors, reduce the total mass of the battery, and improve the energy density. At the same time, the flexible conductive carbon material and the rigid solid electrolyte jointly form a "soft-hard" skeleton, which ensures the flexibility of the negative electrode sheet while further reducing the volume expansion of the silicon-carbon negative electrode. In addition, the prepared paper is a flexible paper that can be quickly cut into any shape and has no obvious expansion during the battery cycle.

[0128] In step (S1):

[0129] In an optional embodiment, the nitrogen-containing molecule is selected from one or more of urea, dicyandiamide, molecules having a triazine structure and hybrid derivatives thereof, amino acids and derived polypeptides thereof;

[0130] Optionally, the molecule having a triazine structure and its hybrid derivatives are selected from 1,2,3-triazine, 1,2,4-triazine, 1,3,5-s-triazine, 1-hydrogen-1,2,4-triazole, 4-hydrogen-1,2,3-triazole, and 4-hydrogen-1,2,4-triazole.

[0131] Optionally, the amino acid and its derivative polypeptide are selected from guanine, leucine, etc., and small molecule peptide chains formed therefrom.

[0132] Optionally, the molar mass of the nitrogen-containing molecule is 10 to 1500 g / mol; specifically, it can be 10 g / mol, 50 g / mol, 100 g / mol, 200 g / mol, 300 g / mol, 400 g / mol, 500 g / mol, 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1200 g / mol, 1300 g / mol, 1400 g / mol, 1500 g / mol or any value within the above range;

[0133] Further optionally, the molar mass of the nitrogen-containing molecule is 10 to 500 g / mol.

[0134] In an optional embodiment, the transition metal salt, the cation includes but is not limited to one or more of Fe(III / II), Co(II), Ni(II), Cu(II), Zn(II), Mn(II), and the anion includes but is not limited to one or more of nitrate ion, chloride ion, and sulfate ion;

[0135] Optionally, the cation is selected from Fe(III) and / or Co(II);

[0136] Optionally, the anion is selected from nitrate ions.

[0137] In an alternative embodiment:

[0138] The mass ratio of the nitrogen-containing molecule to the transition metal salt is 10:(0.1-1.5); specifically, it can be 10:0.1, 10:0.3, 10:0.5, 10:0.8, 10:1.0, 10:1.2, 10:1.5 or any ratio within the above range;

[0139] The carbon nanotubes prepared by the catalytic pyrolysis have an average tube diameter of 100 to 800 nm.

[0140] Optionally, the mass ratio of nitrogen-containing molecules to transition metal salt is 10:(0.25-0.75);

[0141] Further optionally, the mass ratio of the nitrogen-containing molecules to the transition metal salt is 10:(0.25-0.5).

[0142] Experiments have found that by adjusting the mass ratio of nitrogen-containing molecules to transition metal salts, the average diameter of the prepared carbon nanotubes can be controlled, and then the electrochemical properties of the final negative electrode paper and the solid-state battery assembled therein can be regulated.

[0143] In an alternative embodiment:

[0144] The catalytic pyrolysis temperature is 600-1000°C; specifically, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any value within the above range.

[0145] Optionally, the heating rate of catalytic pyrolysis is 2 to 20°C / min; specifically, it can be 2°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min, 20°C / min or any value within the above range.

[0146] Optionally, the holding time for catalytic pyrolysis is 1 to 6 h; specifically, it can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h or any value within the above range.

[0147] Optionally, the crude product obtained after the catalytic pyrolysis reaction is further subjected to acid washing and drying steps;

[0148] Optionally, the acid concentration in the pickling step is 0.1-2 mol / L; specifically, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.0 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L or any value within the above range.

[0149] Optionally, the pickling time is 2 to 20 hours; specifically, it can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or any value within the above range.

[0150] Optionally, the drying temperature is 50-80°C; specifically, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value within the above range.

[0151] Optionally, the drying time is 1 to 10 h; specifically, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the above range.

[0152] In step (S1):

[0153] In an optional embodiment, the physical activation pore formation satisfies at least one of the following A to D:

[0154] A. The physical activation pore forming agent is selected from CO, CO 2 , water vapor, oxygen or one or more thereof;

[0155] Optionally, the activator is selected from CO, CO 2 , water vapor;

[0156] B. The physical activation pore forming, the activator flow rate is 0.1 ~ 20L / min; specifically, it can be 0.1L / min, 0.5L / min, 1L / min, 2L / min, 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min, 12L / min, 14L / min, 16L / min, 18L / min, 20L / min or any value within the above range.

[0157] Optionally, the flow rate of the activator is 5 to 10 L / min.

[0158] C. The physical activation pore forming has a temperature of 600-1200°C; specifically, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value within the above range.

[0159] Optionally, the heating rate is 0.1 to 10°C / min; specifically, it can be 0.1°C / min, 0.5°C / min, 1°C / min, 2°C / min, 5°C / min, 8°C / min, 10°C / min or any value within the above range.

[0160] Further optionally, the heating rate is 1-10° C. / min.

[0161] D. The physical activation pore-forming time is 1 to 15 hours; specifically, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or any value within the above range.

[0162] Optionally, the physical activation pore making is carried out in a rotary kiln, and the rotation speed of the rotary kiln is controlled to be 1 to 20 rpm; specifically, it can be 1 rpm, 2 rpm, 5 rpm, 8 rpm, 10 rpm, 12 rpm, 15 rpm, 18 rpm, 20 rpm or any value within the above range.

[0163] In an optional embodiment, the silicon deposition satisfies at least one of the following a to f:

[0164] a. The silicon deposition, the raw material gas used includes a silicon source gas;

[0165] Optionally, the silicon source gas includes but is not limited to common types such as monosilane, disilane, monochlorosilane, trichlorosilane, etc.;

[0166] b. For the silicon deposition, the flow rate of the raw gas is 1 to 200 L / h; specifically, it can be 1 L / h, 5 L / h, 10 L / h, 20 L / h, 30 L / h, 50 L / h, 80 L / h, 100 L / h, 150 L / h, 200 L / h or any value within the above range.

[0167] Optionally, the flow rate of the raw gas is 50 to 150 L / h.

[0168] c. The silicon deposition temperature is 300-600°C; specifically, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any value within the above range.

[0169] Optionally, the heating rate is 1 to 10°C / min; specifically, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value within the above range.

[0170] d. The silicon deposition time is 1 to 50 hours; specifically, it can be 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours or any value within the above range.

[0171] e. The raw gas also includes a carrier gas;

[0172] Optionally, the carrier gas is nitrogen and / or argon;

[0173] f. Taking the total volume of the raw gas as 100%, the volume proportion of the carrier gas is 1 to 30%; specifically, it can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value within the above range.

[0174] In an optional embodiment, the carbon coating satisfies at least one of the following 1) to 6):

[0175] 1) The carbon coating uses a raw material gas including a carbon-containing gas;

[0176] 2) The carbon-coated carbon-containing gas is selected from one or more of C1-C4 alkanes (methane, ethane, propane, butane), C2-C4 olefins (ethylene, propylene, butene, 1,3-butadiene), and C2-C4 alkynes (acetylene, propyne, butyne);

[0177] 3) For the carbon coating, the flow rate of the raw gas is 1 to 100 L / h; specifically, it can be 1 L / h, 5 L / h, 10 L / h, 20 L / h, 30 L / h, 50 L / h, 80 L / h, 100 L / h or any value within the above range.

[0178] 4) The carbon coating has a temperature of 400-1200°C; specifically, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C or any value within the above range.

[0179] 5) The carbon coating time is 1 to 20 hours; specifically, it can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 20 hours or any value within the above range.

[0180] 6) The carbon coating includes an inert gas in the raw gas, and the volume proportion of the inert gas is 1-30% based on the total volume of the raw gas as 100%; specifically, it can be 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or any value within the above range.

[0181] In step (S2):

[0182] In an optional embodiment, the dispersant is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives;

[0183] In an optional embodiment, the solvent I is selected from deionized water and / or N-methylpyrrolidone;

[0184] In an optional embodiment, in the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode to the dispersant is 10:(0.01-5); specifically, it can be 10:0.01, 10:0.05, 10:0.1, 10:0.5, 10:1.0, 10:1.5, 10:2.0, 10:2.5, 10:3.0, 10:3.5, 10:4.0, 10:4.5, 10:5.0 or any ratio within the above range;

[0185] Optionally, the mass ratio of the silicon-carbon negative electrode to the dispersant is 10:(0.15-0.5);

[0186] Further optionally, the mass ratio of the silicon-carbon negative electrode to the dispersant is 10:(0.25-0.5).

[0187] In an optional embodiment, in the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode to the solvent I is 10:(10-300); specifically, it can be 10:10, 10:20, 10:50, 10:80, 10:100, 10:150, 10:200, 10:250, 10:300 or any ratio within the above range.

[0188] In an optional embodiment, the one-dimensional carbon material is selected from one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon fibers;

[0189] Optionally, when single-walled carbon nanotubes are selected, the intensity of the G band / D band in the Raman spectrum thereof is not less than 5, the average length is not less than 100 μm, and the diameter is 2 to 15 nm;

[0190] Optionally, when other one-dimensional carbon materials are selected, the G-band / D-band intensity is not less than 1, the length is not less than 5 μm, and the diameter is not higher than 50 nm.

[0191] In an optional embodiment, the two-dimensional carbon material is selected from graphene oxide;

[0192] Optionally, the two-dimensional graphene oxide is prepared by a Hammer method, and has an oxygen content of not less than 20%.

[0193] In an optional embodiment, the solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium silicon oxide, and lithium lanthanum titanium oxide;

[0194] In an optional embodiment, the polymer is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives;

[0195] In an optional embodiment, the solvent II is selected from deionized water and / or N-methylpyrrolidone;

[0196] In an optional embodiment, in the electronic / ion conductive slurry B, the mass ratio of the conductive carbon material to the solid electrolyte is 1:(0.1-10); specifically, it can be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any ratio within the above range;

[0197] In the electronic / ion conductive paste B, the mass ratio of the conductive carbon material to the polymer is 1:(0.1-10); specifically, it can be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any ratio within the above range;

[0198] In the electronic / ion conductive slurry B, the mass ratio of the conductive carbon material to the solvent II is 1:(10-300); specifically, it can be 1:10, 1:20, 1:50, 1:80, 1:100, 1:150, 1:200, 1:250, 1:300 or any ratio within the above range;

[0199] Optionally, the mass ratio of the conductive carbon material, the solid electrolyte, the polymer and the solvent II is 1:(0.5-5):(0.5-5):(10-100);

[0200] In an optional embodiment, the mass ratio of the one-dimensional carbon material to the two-dimensional carbon material is 1:(0-1);

[0201] Optionally, the mass ratio of the one-dimensional carbon material to the two-dimensional carbon material is 1:(0.01~0.5); specifically, it can be 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or any ratio within the above range; further optionally, the mass ratio of the one-dimensional carbon material to the two-dimensional carbon material is 1:(0.01~0.1).

[0202] Experiments have shown that the additional introduction of two-dimensional carbon materials can further improve the conductivity of the system, and the first coulombic efficiency, cycle retention rate and rate performance of the finally assembled solid-state battery are all improved.

[0203] Comparative tests have shown that using only two-dimensional carbon materials or three-dimensional carbon materials (such as acetylene black) to replace one-dimensional carbon materials will lead to deterioration of the cycle retention rate and rate performance of the final assembled solid-state battery.

[0204] In an optional embodiment, the nanocellulose has a diameter of 1 to 50 nm and a length of 30 to 100 μm;

[0205] In an optional embodiment, the solvent III is selected from deionized water and / or N-methylpyrrolidone;

[0206] In an optional embodiment, the solid content of the fiber dispersion emulsion C is 1 to 50 wt%; specifically, it can be 1 wt%, 3 wt%, 5 wt%, 8 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt% or any value within the above range.

[0207] In an optional embodiment, the mass ratio of the silicon-carbon dispersion A to the electronic / ion conductive paste B is 10:(1-10); specifically, it can be 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:5, 10:5.5, 10:8, 10:8.5, 10:10 or any ratio within the above range;

[0208] In an optional embodiment, the mass ratio of the silicon-carbon dispersion A to the fiber dispersion emulsion C is 10:(1-10); specifically, it can be 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:5, 10:5.5, 10:8, 10:8.5, 10:10 or any ratio within the above range;

[0209] Optionally, the mass ratio of the silicon-carbon dispersion A, the electronic / ion conductive slurry B and the fiber dispersion emulsion C is 10:(2.5-5):(2.5-5);

[0210] The experiment found that by optimizing the ratio of the above raw materials in the papermaking pulp, the electrochemical performance of the final prepared negative electrode paper and the solid-state battery assembled therein can be regulated;

[0211] Further optionally, the mass ratio of the silicon-carbon dispersion A, the electron / ion conductive slurry B and the fiber dispersion emulsion C is 10:5:5.

[0212] Optionally, the mixing and dispersing has a dispersion rate of 500 to 3000 rpm; specifically, it can be 500 rpm, 600 rpm, 800 rpm, 1000 rpm, 1200 rpm, 1500 rpm, 1800 rpm, 2000 rpm, 2500 rpm, 3000 rpm or any value within the above range.

[0213] Optionally, the mixing and dispersing time is controlled at 0.5 to 10 h; specifically, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value within the above range.

[0214] In step (S2):

[0215] In an optional embodiment, the fiber dispersion emulsion C satisfies at least one of the following (1) to (2):

[0216] (1) The fiber dispersion emulsion C also includes elastic fibers;

[0217] Optionally, the elastic fiber is selected from one or more of polytetrafluoroethylene fiber, polyvinylidene fluoride fiber, and polysiloxane fiber;

[0218] Optionally, the mass ratio of nanocellulose to elastic fiber is (0.2-5):1; specifically, it can be 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any ratio within the above range.

[0219] Optionally, firstly, nanocellulose is dispersed in solvent III to obtain nanocellulose dispersion, then elastic fibers are dispersed in solvent III to obtain elastic fiber dispersion, and finally the two are evenly mixed to obtain fiber dispersion emulsion C;

[0220] Optionally, the concentration of the nanocellulose dispersion is 0.1-10wt%; specifically, it can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 8wt%, 10wt% or any value within the above range.

[0221] Optionally, the concentration of the elastic fiber dispersion is 0.1-10wt%; specifically, it can be 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 8wt%, 10wt% or any value within the above range.

[0222] Optionally, the volume ratio of the nanocellulose dispersion to the elastic fiber dispersion is (0.2-5):1; specifically, it can be 0.2:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any ratio within the above range.

[0223] Experiments have found that the introduction of elastic fibers further improves the stability of the negative electrode sheet, giving it certain mechanical properties while also making it flexible, so that the negative electrode sheet can be cut arbitrarily without causing structural defects, and the elastic fibers can further overcome the volume expansion of silicon-carbon.

[0224] (2) The nanocellulose is subjected to copper modification treatment, specifically comprising:

[0225] The nanocellulose is immersed in a copper salt aqueous solution, and after washing, the copper-modified nanocellulose is obtained;

[0226] Optionally, the concentration of the copper salt aqueous solution is 1 to 20 wt%; specifically, it can be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 8 wt%, 10 wt%, 12 wt%, 15 wt%, 18 wt%, 20 wt% or any value within the above range.

[0227] Optionally, the anion of the selected copper salt includes, but is not limited to, one or more of nitrate, chloride, and sulfate.

[0228] In step (S3):

[0229] In an optional embodiment, the amine-based small molecule reducing agent is selected from hydrazine hydrate and / or ethylenediamine;

[0230] Optionally, the amino-based small molecule reducing agent is selected from hydrazine hydrate with stronger reducing properties.

[0231] In an optional embodiment, the amine-based small molecule reducing agent is subjected to reduction treatment in a vapor state;

[0232] In an optional embodiment, the steam containing the amine-based small molecule reducing agent also includes water vapor;

[0233] In an optional embodiment, based on the total mass of the steam as 100%, the mass fraction of the amine-based small molecule reducing agent is 0.1-3%; specifically, it can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0% or any value within the above range;

[0234] Optionally, the mass fraction of the amine-based small molecule reducing agent is 1-2%.

[0235] In an optional embodiment, the reduction treatment temperature is 80-120°C; specifically, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value within the above range.

[0236] Optionally, the reduction treatment time is 5 to 12 h; specifically, it can be 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or any value within the above range.

[0237] In a second aspect, the present invention also provides a flexible negative electrode paper for solid-state batteries prepared according to the method.

[0238] In a third aspect, the present invention further provides a negative electrode plate, which is prepared by impregnating the flexible negative electrode paper for solid-state batteries with an electrolyte.

[0239] In a fourth aspect, the present invention further provides a solid-state battery, comprising the negative electrode plate described above.

[0240] Example 1

[0241] (S1) Preparation of silicon-carbon negative electrode:

[0242] 20 kg of melamine and 1 kg of cobalt nitrate powder were mixed in a mixer for 2 hours and then put into a tubular furnace, the oxygen content was controlled to be below 50 ppm, and then the temperature was increased to 800°C at a heating rate of 10°C / min and kept warm for 2 hours. After the material was cooled, it was taken out and immersed in a 1 mol / L hydrochloric acid solution. The pickling time was controlled to be 5 hours. After the material was washed with water until neutral, excess water was filtered out by pressure. The filter cake was dried at 60°C for 5 hours to obtain a dry product, and then the dry product was dispersed using a disperser to obtain carbon tubes;

[0243] 10 kg of carbon tubes were placed in a rotary furnace, the furnace speed was controlled to be 5 rpm, the oxygen content was below 50 ppm, the temperature was raised to 700 °C at 5 °C / min, and then water vapor was introduced at a flow rate of 10 L / min and kept warm for 4 hours. After the reaction was completed, the water vapor supply was cut off, and the activated carbon tubes were obtained after cooling;

[0244] Through transmission electron microscopy (TEM) detection, the average diameter of the activated carbon tubes prepared in this embodiment is distributed in the range of 200 to 400 nm;

[0245] 5kg of activated carbon tubes were placed in a rotary kiln, the furnace speed was controlled to be 5rpm, the oxygen content was below 30ppm, the temperature was raised to 500°C at 5°C / min, and then 100L / h of monosilane gas was introduced and kept warm for 20h, of which nitrogen accounted for 2%, and the temperature was continued to be raised to 650°C at 5°C / min, and then 50L / h of acetylene gas was introduced and kept warm for 5h, of which nitrogen accounted for 20%, and the material was taken out after cooling to obtain a silicon-carbon negative electrode;

[0246] (S2) Papermaking Pulp Preparation

[0247] Preparation of silicon-carbon dispersion A: 100 g of the silicon-carbon negative electrode prepared in step (S1), 2.5 g of carboxymethyl cellulose and 500 g of water were mixed and dispersed (wherein the total solid content was 17% and the silicon-carbon negative electrode content was 16.6%);

[0248] Preparation of electronic / ionic conductive slurry B: 5 g of single-walled carbon nanotubes, 2 g of multi-walled carbon nanotubes, 4 g of lithium lanthanum zirconium oxide, 4 g of polyethylene oxide, and 400 g of water were mixed and dispersed (total solid content was about 3.6%);

[0249] Preparation of fiber dispersion emulsion C: 10 g of nanocellulose (CNF-C) was dispersed in 190 g of water;

[0250] Preparation of papermaking pulp: 100g silicon-carbon dispersion A, 50g electronic / ion conductive slurry B, and 50g fiber dispersion emulsion C are mixed and stirred for dispersion at a dispersion rate of 1000rpm and a dispersion time of 5h;

[0251] (S3) Negative Electrode Paper Preparation

[0252] The papermaking slurry obtained in step (S2) was scraped onto a polytetrafluoroethylene board and dried at 70°C for 5 hours to obtain preliminary negative electrode paper. Subsequently, the negative electrode paper was reduced in hydrazine hydrate-containing water vapor (the mass fraction of hydrazine hydrate was 1.5%) at 80°C for 8 hours, and then rolled to obtain the final negative electrode paper. The thickness of the negative electrode paper was tested to be 96.3 μm.

[0253] Example 2

[0254] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of the cobalt nitrate powder is replaced with 0.5 kg.

[0255] According to TEM detection, the average diameter of the activated carbon tubes prepared in this embodiment is distributed in the range of 400-600 nm. The thickness of the prepared negative electrode paper is 97.1 μm.

[0256] Example 3

[0257] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of the cobalt nitrate powder is replaced with 1.5 kg.

[0258] According to TEM detection, the average diameter of the activated carbon tubes prepared in this embodiment is distributed in the range of 100-200 nm. The thickness of the prepared negative electrode paper is 96.5 μm.

[0259] Example 4

[0260] The preparation process is substantially the same as that of Example 1, except that in step (S1), the cobalt nitrate powder is replaced with an equal mass of nickel nitrate powder.

[0261] According to TEM detection, the average diameter of the activated carbon tubes prepared in this embodiment is distributed in the range of 200-400 nm. The thickness of the prepared negative electrode paper is 96.8 μm.

[0262] Example 5

[0263] The preparation process is substantially the same as that of Example 1, except that in step (S1), the flow rate of monosilane gas is replaced with 50 L / h.

[0264] After testing, the thickness of the prepared negative electrode paper was 96.7μm.

[0265] Example 6

[0266] The preparation process is substantially the same as that of Example 1, except that in step (S1), the flow rate of monosilane gas is replaced with 150 L / h.

[0267] After testing, the thickness of the prepared negative electrode paper was 96.2μm.

[0268] Example 7

[0269] The preparation process is basically the same as that of Example 1, except for the preparation of the electronic / ion conductive paste B in step (S2):

[0270] 5 g of single-walled carbon nanotubes, 2 g of multi-walled carbon nanotubes, 0.1 g of graphene oxide, 4 g of lithium lanthanum zirconium oxide, 4 g of polyethylene oxide, and 400 g of water were mixed and dispersed.

[0271] After testing, the thickness of the prepared negative electrode paper was 95.3μm.

[0272] Example 8

[0273] The preparation process is basically the same as that of Example 7, except for the preparation of the fiber dispersion emulsion C in step (S2):

[0274] Dispersing 10 g of nanocellulose in 190 g of water to obtain a nanocellulose dispersion;

[0275] Dispersing 10 g of polytetrafluoroethylene fiber into 190 g of water to obtain a polytetrafluoroethylene fiber dispersion;

[0276] The nanocellulose dispersion and the polytetrafluoroethylene fiber dispersion of equal weight were fully mixed and dispersed. After testing, the thickness of the prepared negative electrode paper was 95.8 μm.

[0277] Example 9

[0278] The preparation process is basically the same as that of Example 7, except for the preparation of the fiber dispersion emulsion C in step (S2):

[0279] 10 g of nanocellulose was immersed in 110 g of copper nitrate aqueous solution (concentration of 9 wt%), and after 24 h, the nanocellulose was taken out and rinsed three times with deionized water to ensure that the copper salt was removed, thereby obtaining copper-modified nanocellulose;

[0280] Dispersing 10 g of copper-modified nanocellulose in 190 g of water to obtain a copper-modified nanocellulose dispersion;

[0281] Dispersing 10 g of polytetrafluoroethylene fiber into 190 g of water to obtain a polytetrafluoroethylene fiber dispersion;

[0282] Equal masses of copper-modified nanocellulose dispersion and polytetrafluoroethylene fiber dispersion were fully mixed and dispersed.

[0283] After testing, the thickness of the prepared negative electrode paper was 95.8μm.

[0284] Example 10

[0285] The preparation process is basically the same as that of Example 1, except that in the preparation of the silicon-carbon dispersion A in step (S2), the mass of carboxymethyl cellulose is replaced with 1.5 g.

[0286] After testing, the thickness of the prepared negative electrode paper was 95.3μm.

[0287] Embodiment 11

[0288] The preparation process is basically the same as that of Example 1, except that in the preparation of papermaking pulp in step (S2), the mass of the electronic / ion conductive slurry B is replaced with 25 g.

[0289] After testing, the thickness of the prepared negative electrode paper was 92.3μm.

[0290] Example 12

[0291] The preparation process is basically the same as that of Example 1, except that in the preparation of papermaking pulp in step (S2), the mass of fiber dispersion emulsion C is replaced with 25 g.

[0292] After testing, the thickness of the prepared negative electrode paper was 93.4μm.

[0293] Embodiment 13

[0294] The preparation process is substantially the same as that of Example 1, except that in step (S3), the hydrazine hydrate vapor is replaced by ethylenediamine vapor (the mass fraction is still 1.5%, and the temperature is 100° C.).

[0295] After testing, the thickness of the prepared negative electrode paper was 96.3μm.

[0296] Comparative Example 1

[0297] The preparation process is substantially the same as that of Example 1, except that in step (S1), the mass of the cobalt nitrate powder is replaced with 3 kg.

[0298] According to TEM detection, the average diameter of the activated carbon tubes prepared in this comparative example is distributed in the range of 10 to 50 nm.

[0299] After testing, the thickness of the prepared negative electrode paper was 97.1μm.

[0300] Comparative Example 2

[0301] The preparation process is basically the same as that of Example 1, except that in step (S2), the preparation of the electronic / ion conductive paste B is:

[0302] 7 g of graphene oxide, 4 g of lithium lanthanum zirconium oxide, 4 g of polyethylene oxide, and 400 g of water were mixed and dispersed.

[0303] After testing, the thickness of the prepared negative electrode paper was 96.7μm.

[0304] Comparative Example 3

[0305] The preparation process is basically the same as that of Example 1, except that in step (S2), the preparation of the electronic / ion conductive paste B is:

[0306] Mix and disperse 7g of acetylene black, 4g of lithium lanthanum zirconium oxide, 4g of polyethylene oxide, and 400g of water.

[0307] After testing, the thickness of the prepared negative electrode paper was 95.9μm.

[0308] Comparative Example 4

[0309] The preparation process is basically the same as that of Example 1, except that in step (S3), the papermaking slurry obtained in step (S2) is scraped onto a polytetrafluoroethylene plate and dried at 70° C. for 5 h to obtain the negative electrode paper.

[0310] After testing, the thickness of the prepared negative electrode paper was 105.3μm.

[0311] The specific test data of the silicon-carbon negative electrode materials prepared in step S1 of each embodiment of the present invention and the comparative example are shown in Table 1 below, wherein the silicon content is converted from the thermogravimetric curve in air (the conversion method is: Si% = M 1 ×100%×0.467 / M 0 , where M 0 and M 1 are the masses of the test sample at room temperature and 1000°C, respectively; 0.467 is the mass ratio of silicon in silicon dioxide; the powder resistance is measured by a four-terminal powder resistivity tester (ST2722B); and the specific surface area is obtained by a precision high-performance nitrogen adsorption and desorption test system (JW-HB100).

[0312] Table 1

[0313]

[0314] In each embodiment of the present invention, since the dispersion stability of the papermaking slurry affects the electrochemical properties of the final negative electrode paper, it is necessary to test the dispersion stability of the papermaking slurry prepared in step S2. The test method is a dilution precipitation method. The specific steps are: take 20g of papermaking slurry and add it to a 200mL glass conical bottle, then add deionized water to dilute it to 5 times the original. At this time, the solid content of the dispersion is γ 0, cover the bottle mouth with plastic wrap, ultrasonicate in a 10W ultrasonic tank for 10 minutes, and then place it in a 25℃ constant temperature box for 24 hours. After 24 hours, discard the lower precipitate. At this time, the solid content of the supernatant is γ 1 , calculate the ratio of solid content before and after precipitation, and obtain the value Q related to the dispersion stability of the slurry, that is, Q = γ 1 / γ 0 The closer the Q value is to 1, the better the dispersion stability is.

[0315] The thickness of the negative electrode paper was measured using a micrometer.

[0316] The resistance of the negative electrode paper was tested using a blocking electrode. The detection method was as follows: the negative electrode paper was cut and punched into small discs with a diameter of 12 mm. The discs were sandwiched between two stainless steel sheets. The whole was clamped with an alligator clip and then a universal ammeter was used to perform a resistance test. The thickness reading shown by the micrometer was then normalized to obtain the resistance (Ω / cm).

[0317] The solid-state full battery assembled with the negative electrode paper prepared in each embodiment and comparative example was tested, and the specific test method was as follows:

[0318] ① Preparation of positive electrode sheet: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), conductive agent SuperP, carbon nanotubes, binder polyvinylidene fluoride (PVDF) are mixed with N-methylpyrrolidone (NMP) at a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70wt%), which is coated on the front and back sides of the current collector aluminum foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, striped, and welded to the tabs to form a positive electrode sheet. The preparation of the diaphragm electrolyte is as follows. Preparation of negative electrode sheet: The negative electrode paper is trimmed, cut, and stripped, and the tabs are welded to make negative electrode sheets (the negative electrode paper is soaked in the electrolyte for 3 hours in the dark and then dried at 60°C. The electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M)). Preparation of solid electrolyte film: 5g polyvinylidene fluoride (PVDF), 10g polyethylene oxide (PEO), 5g lithium bistrifluoromethylsulfonyl imide (LiTFSI) and 5g solid electrolyte lithium lanthanum zirconium tantalum oxide (LLZTO) are added to 110g DMF in sequence. After stirring for 12 hours, the slurry is evenly coated on the PET substrate using a highly adjustable scraper. Finally, vacuum drying is performed at 55°C for 24 hours, and the PET template is removed to obtain the LLZTO / PVDF / PEO solid electrolyte membrane.

[0319] ②Using LLZTO / PVDF / PEO solid electrolyte membrane as the separator, the prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare cell; the bare cell is placed in an aluminum-plastic shell package and placed in a relative vacuum pressure of -0.95×10 5 Pa, dried at 100°C until the moisture content is below 100ppm, and then the battery is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity division) to make a soft-pack solid-state lithium-ion battery.

[0320] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.

[0321] ③ The battery cycle performance was tested on the Xinwei equipment, specifically: at 25°C, first discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, calculate the capacity retention rate after 100 cycles, and compare the expansion displacement of the pole piece before and after the cycle to get the expansion rate. The 3C reversible specific capacity is after the above rate test is performed for 5 cycles, and 0.1C is converted to 3C. See Table 2 for specific test / calculation results.

[0322] Table 2

[0323]

[0324]

[0325] From the comparison of Examples 1 to 13 in Table 2, it can be seen that the solid-state batteries assembled with the negative electrode materials prepared in each Example have excellent cycle stability, rate performance and low expansion rate, among which the electrochemical performance of the product prepared in Example 9 is the best.

[0326] Comparing Examples 1 to 3 with Comparative Example 1, the cycle and rate performance of the solid-state battery assembled with the negative electrode material prepared in Example 3 is slightly lower; the reason may be that the diameter of the porous carbon nanotubes used as the substrate is thinner, the pore volume is low after activation, and the same amount of silicon deposition is easy to float silicon, resulting in an increase in the powder resistance of the negative electrode material, thereby affecting its cycle and rate performance. The cycle and rate performance of the solid-state battery assembled with the negative electrode material prepared in Comparative Example 1 is significantly reduced, which may be due to the fact that the diameter of the porous carbon nanotubes used as the substrate is too thin, which is only equivalent to the pore diameter of conventional carbon nanotubes (10 to 50 nm).

[0327] By comparing Examples 1, 5 and 6, it can be seen that the amount of deposited silicon affects the electrochemical performance. The more silicon content, the higher the capacity, but the resistance and electrochemical expansion will be higher.

[0328] By comparing Examples 1 and 7 to 9, it can be seen that due to the addition of two-dimensional conductive carbon material (Example 7), its conductivity in the plane is increased, and the first coulomb efficiency, cycle retention rate and rate performance are all improved; due to the addition of elastic fiber body (Example 8), the negative electrode paper is made softer and the expansion rate after cycle is lower; due to the addition of elastic fiber body and the copper modification of nanocellulose (Example 9), copper doping opens the strong hydrogen bonds of cellulose, so that it has effective lithium ion transport function, and the rate performance and cycle retention rate are improved.

[0329] By comparing Examples 1 and 10, it can be seen that the reduced usage of the silicon-carbon negative electrode dispersant results in lower dispersion stability of the papermaking pulp and uneven negative electrode paper, which leads to a decrease in its electrochemical performance.

[0330] By comparing Examples 1 and 11 to 12, it can be seen that the usage of the electronic / ion conductive agent slurry B and the fiber dispersion emulsion C are respectively reduced. A reduction in the usage of either one will lead to a decrease in the dispersion stability of the papermaking pulp; a reduction in the usage of the electronic / ion conductive agent slurry B will lead to a higher resistance of the negative electrode paper. Although the capacity is improved, the first coulomb efficiency and rate capacity are low, and the expansion rate is large; a reduction in the usage of the fiber dispersion emulsion C will result in a significant increase in the expansion rate on the basis of the low first coulomb efficiency and rate capacity.

[0331] By comparing Examples 1 and 13, it can be seen that the reducing property of ethylenediamine vapor as the reducing agent is weaker than that of hydrazine hydrate vapor, so the resistance is slightly higher, but the electrochemical performance is still at the same level as that of Example 1.

[0332] By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that since the one-dimensional conductive carbon material is replaced by a two-dimensional conductive carbon material (Comparative Example 2) and a three-dimensional conductive carbon material (Comparative Example 3), respectively, the cycle retention rate and rate of the solid-state battery assembled with the prepared negative electrode material are significantly reduced.

[0333] By comparing Example 1 and Comparative Example 4, it can be seen that the resistance of the negative electrode paper is significantly increased and the comprehensive electrochemical performance is significantly reduced due to the lack of reduction treatment.

[0334] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.

Claims

1. A method for preparing a flexible negative electrode paper for a solid-state battery, characterized in that: include: (S1) uniformly mixing nitrogen-containing molecules and transition metal salts, obtaining carbon nanotubes through catalytic pyrolysis reaction, and then obtaining porous carbon nanotubes through physical activation and pore formation; using the porous carbon nanotubes as a substrate, sequentially performing silicon deposition and carbon coating to obtain a silicon-carbon negative electrode; (S2) mixing a silicon-carbon negative electrode, a dispersant and a solvent I to obtain a silicon-carbon dispersion A; mixing a conductive carbon material, a solid electrolyte, a polymer and a solvent II to obtain an electronic / ion conductive slurry B; mixing nanocellulose with a solvent III to obtain a fiber dispersion emulsion C; mixing and dispersing the silicon-carbon dispersion A, the electronic / ion conductive slurry B and the fiber dispersion emulsion C to obtain a papermaking pulp; The conductive carbon material includes a one-dimensional carbon material and an optionally added two-dimensional carbon material; (S3) The papermaking slurry is coated on a substrate, and is reduced with an amine-containing small molecule reducing agent to obtain the flexible negative electrode paper for solid-state batteries.

2. The method for preparing a flexible negative electrode paper for a solid-state battery according to claim 1, characterized in that: In step (S1): The nitrogen-containing molecule is selected from one or more of urea, dicyandiamide, molecules having a triazine structure and hybrid derivatives thereof, amino acids and derived polypeptides thereof; The transition metal salt, cations include but are not limited to one or more of Fe(III / II), Co(II), Ni(II), Cu(II), Zn(II), Mn(II), and anions include but are not limited to one or more of nitrate, chloride, and sulfate; The mass ratio of nitrogen-containing molecules to transition metal salts is 10:(0.1-1.5); The catalytic pyrolysis temperature is 600-1000°C; The carbon nanotubes prepared by the catalytic pyrolysis have an average tube diameter of 100 to 800 nm.

3. The method for preparing a flexible negative electrode paper for a solid-state battery according to claim 1, characterized in that: In step (S1), the physical activation pore formation satisfies at least one of the following A to D: A. The physical activation pore formation, the activator is selected from one or more of CO, CO2, water vapor, and oxygen; B. The physical activation pore formation, the activator flow rate is 0.1 ~ 20L / min; C. The physical activation pore-forming process has a temperature of 600 to 1200°C; D. The physical activation pore-forming time is 1 to 15 hours; The silicon deposition satisfies at least one of the following a to f: a. The silicon deposition, the raw material gas used includes a silicon source gas; b. The silicon deposition, the flow rate of the raw gas is 1 to 200 L / h; c. The silicon is deposited at a temperature of 300 to 600°C; d. The silicon deposition time is 1 to 50 hours; e. The raw gas also includes a carrier gas; f. Taking the total volume of the raw gas as 100%, the volume of the carrier gas accounts for 1 to 30%; The carbon coating satisfies at least one of the following 1) to 6): 1) The carbon coating uses a raw material gas including a carbon-containing gas; 2) The carbon-coated carbon-containing gas is selected from one or more of C1-C4 alkanes, C2-C4 alkenes, and C2-C4 alkynes; 3) The carbon coating has a flow rate of 1 to 100 L / h of raw gas; 4) The carbon coating is carried out at a temperature of (400-1200)°C; 5) The carbon coating time is 1 to 20 hours; 6) In the carbon coating, the raw gas also includes an inert gas, and the volume proportion of the inert gas is 1 to 30% based on the total volume of the raw gas as 100%.

4. The method for preparing a flexible negative electrode paper for a solid-state battery according to claim 1, characterized in that: In step (S2), The dispersant is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives; The solvent I is selected from deionized water and / or N-methylpyrrolidone; In the silicon-carbon dispersion A, the mass ratio of the silicon-carbon negative electrode, the dispersant and the solvent I is 10:(0.01-5):(10-300); The one-dimensional carbon material is selected from one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, few-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon fibers; The two-dimensional carbon material is selected from graphene oxide; The solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, lithium lanthanum zirconium silicon oxide, and lithium lanthanum titanium oxide; The polymer is selected from one or more of carboxymethyl cellulose and its derivatives, polyacrylic acid and its derivatives, polyamide and its derivatives, polyalkanoic acid and its derivatives, polyvinylidene fluoride and its derivatives, polyoxyethylene and its derivatives, polyvinyl alcohol and its derivatives; The solvent II is selected from deionized water and / or N-methylpyrrolidone; In the electronic / ion conductive slurry B, the mass ratio of the conductive carbon material, the solid electrolyte, the polymer and the solvent II is 1:(0.1-10):(0.1-10):(10-300); The mass ratio of one-dimensional carbon material to two-dimensional carbon material is 1:(0-1); The nanocellulose has a diameter of 1 to 50 nm and a length of 30 to 100 μm; The solvent III is selected from deionized water and / or N-methylpyrrolidone; The solid content of the fiber dispersion emulsion C is 1 to 50 wt %; The mass ratio of the silicon-carbon dispersion A, the electron / ion conductive slurry B and the fiber dispersion emulsion C is 10:(1-10):(1-10).

5. The method for preparing a flexible negative electrode paper for a solid-state battery according to claim 1, characterized in that: In step (S2), the fiber dispersion emulsion C satisfies at least one of the following (1) to (2): (1) The fiber dispersion emulsion C also includes elastic fibers; The elastic fiber is selected from one or more of polytetrafluoroethylene fiber, polyvinylidene fluoride fiber, and polysiloxane fiber; The mass ratio of nanocellulose to elastic fiber is (0.2-5):1; (2) The nanocellulose is subjected to copper modification treatment, specifically comprising: The nanocellulose is immersed in a copper salt aqueous solution, and after washing, the copper-modified nanocellulose is obtained; The concentration of the copper salt aqueous solution is 1-20 wt %.

6. The method for preparing a flexible negative electrode paper for a solid-state battery according to claim 1, characterized in that: In step (S3), The amino small molecule reducing agent is selected from hydrazine hydrate and / or ethylenediamine; The amine-based small molecule reducing agent is subjected to reduction treatment in a vapor state; The vapor containing the amino-based small molecule reducing agent also includes water vapor; Based on the total mass of the steam being 100%, the mass fraction of the amine-based small molecule reducing agent is 0.1 to 3%; The temperature of the reduction treatment is 80-120°C.

7. The method for preparing a flexible negative electrode paper for a solid-state battery according to any one of claims 1 to 6, characterized in that: In step (S1), the mass ratio of nitrogen-containing molecules to transition metal salt is 10:(0.25-0.75); In step (S2), the mass ratio of the silicon-carbon dispersion A, the electron / ion conductive slurry B and the fiber dispersion emulsion C is 10:(2.5-5):(2.5-5).

8. A flexible negative electrode paper for solid-state batteries prepared according to the method according to any one of claims 1 to 7.

9. A negative electrode plate, characterized in that: The flexible negative electrode paper for solid-state batteries according to claim 8 is prepared by impregnating the paper with electrolyte.

10. A solid-state battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Flexible whole-solid-state battery and preparation method of same

    CN107749491A

  • Preparation method of lithium-philic carbon nanotube paper and preparation method of composite metal lithium negative electrode

    CN112176772A

  • Paper-based silicon carbon negative electrode as well as preparation method and application thereof

    CN119050303A

  • Storage bag balance mounting system for two-wheeled vehicles

    KR102693124B1

  • Self-supporting electrode membrane, secondary battery and device

    WO2024198543A1